2021
DOI: 10.1002/app.51847
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of PVDF/PVA polymer blend film doped with different concentration of NiO NPs for photocatalytic degradation of malachite green dye under visible light

Abstract: Structural, optical and photodegradation performance of PVDF/PVA polymer blend doped with different concentration of NiO NPs were studied using casting technique method. The effect of adding NiO NPs on PVDF/PVA are investigated using X-ray Diffraction (XRD), High Resolution Transmission Electron Microscope (HRTEM), Fourier Transform Infrared-Attenuated Total Reflection (FTIR-ATR), Ultraviolet-Visible Spectroscopy (UV-Vis), and High Resolution Scanning Electron Microscope (HRSEM). XRD results showed that the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…36-1451). , The 35.84°, 61.77°, and 75.53° angles corresponding to the (111), (220), and (311) planes are attributed to NiO (JCPDS file no. 65-2901). , The 27.32°, 39.02°, and 53.96° angles corresponding to the (110), (200), and (211) planes are attributed to RuO 2 (JCPDS no. 40-1290). Considering these results, it was concluded that the crystal lattice structure of trimetallic bt RNZn NPs is a hexagonal wurtzite structure based on the peak density attributed to ZnO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…36-1451). , The 35.84°, 61.77°, and 75.53° angles corresponding to the (111), (220), and (311) planes are attributed to NiO (JCPDS file no. 65-2901). , The 27.32°, 39.02°, and 53.96° angles corresponding to the (110), (200), and (211) planes are attributed to RuO 2 (JCPDS no. 40-1290). Considering these results, it was concluded that the crystal lattice structure of trimetallic bt RNZn NPs is a hexagonal wurtzite structure based on the peak density attributed to ZnO.…”
Section: Resultsmentioning
confidence: 99%
“…65-2901). 62,63 The 27.32°, 39.02°, and 53.96°angles corresponding to the (110), (200), and (211) planes are attributed to RuO 2 (JCPDS no. 40-1290).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…40,51–53 The absorption bands in the spectrum correspond to the different crystalline phases, with bands at 614 cm −1 , 761 cm −1 , 879 cm −1 , 979 cm −1 , and 1068 cm −1 corresponding to the α-phase, and bands at 840 cm −1 , 1180 cm −1 , and 1402 cm −1 corresponding to the β-phase. 52–54 It is found that the pure PVDF polymer is composed mainly of α and β-phases. The γ-phase is challenging to identify as it is not associated with unique FTIR bands.…”
Section: Resultsmentioning
confidence: 99%
“…Darbandi et al 15 examined surfactantassisted PVDF membrane for the removal of azo dye and found that the removal of PVDF modified by Tween 60 is about 96%. Ismail et al 16 prepared PVDF/PVA membrane based on NiO for the removal of malachite green dye (95.4% removal).…”
mentioning
confidence: 99%
“…Dye removal from wastewater is accomplished using various methods. Chemical methods include chemical oxidation, 16 ozonation, 17 physical methods including membrane separation, 18 photocatalytic degradation, 19,20 and adsorption. 21 Photocatalysis is gaining traction as a viable technology strategy across a variety of sectors due to its lower cost and low environmental impact.…”
mentioning
confidence: 99%